Latent profiles and associated factors of workplace violence among nurses in tertiary hospitals: a cross-sectional study - Zhou, Sumei; Zeng, Zhi (Frontiers in Psychiatry, 2025)
BackgroundWorkplace violence (WPV) is a significant occupational hazard that threatens nurses’ psychological well-being and professional stability. Although prior studies have addressed the impact of WPV on nurses, the latent heterogeneity of their violence exposure patterns has not been systematically explored. Moreover, empirical evidence regarding the role of individual psychological traits in shaping different WPV experiences remains limited.ObjectiveThis study aimed to identify latent profiles of WPV exposure among nurses and examine the associations between profile membership and demographic as well as psychological factors, in order to uncover key predictors of distinct WPV patterns.MethodsA cross-sectional survey was conducted between March and May 2025 among 549 registered nurses from eight tertiary hospitals in Sichuan Province, China. Participants completed a battery of standardized instruments, including General Demographic Data Scale, Workplace violence Scale, Maslach Burnout Inventory, Connor-Davidson Resilience Scale, Emotional Labor Scale, and Perceived Organizational Support Scale. Latent Profile Analysis (LPA) was performed using Mplus 8.3 to identify WPV exposure subgroups, and multivariate logistic regression was used to determine associated factors.ResultsLPA revealed two distinct WPV profiles: a high-frequency, multi-type violence group (n = 152, 27.7%) and a low-frequency, mild violence group (n = 397, 72.3%). Nurses in the high-frequency group reported significantly higher scores across all WPV dimensions, including verbal abuse, sexual harassment, threats, and physical assault (P < 0.001). Logistic regression analysis indicated that having a bachelor’s degree or higher, lower salary satisfaction, and lower psychological resilience were significant predictors of membership in the high-frequency WPV group (P < 0.01).ConclusionNurses’ WPV experiences exhibit distinct latent profiles. Educational level, salary satisfaction, and psychological resilience are key differentiating variables. These findings highlight the need for stratified risk identification and targeted interventions, particularly for nurses with higher education levels, low salary satisfaction, and reduced psychological resilience, in order to mitigate the adverse effects of WPV and enhance occupational adaptation.